TINJAUAN YURIDIS TERHADAP PEMBATALAN HIBAH SEBIDANG TANAH MENURUT HUKUM ISLAM PUTUSAN (PERKARA NOMOR 168/PDT.G/2009/PA.PBR) - Tambunan, Edy Putra; Hanifah, Mardalena; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
The understanding grant pursuant to Article 171 paragraph g Presidential InstructionNo. 1 of 1991 Compilation of Islamic Law in defining the grant is granting an objectvoluntarily without adaimbalan from one person to another are still alive to have. Compilationof Islamic Law stipulated that grant requirements, penghibah has also 21 years of age,sensible and based on voluntarism and much - much 1/3 of his property as provided for inArticle 210 Compilation of Islamic Law. While grants are made by parents to their children,their children can be taken into account as an inheritance, when her parents died as stipulatedin Article 211 Compilation of Islamic Law while regarding the withdrawal of the grant of thetreasure that has been granted is not possible for the withdrawal, unless the grant is donepeople parents to their children as stipulated in Article 213 Compilation of Islamic Law.Grant also has a social function in people's lives both given individuals andinstitutions, the function of the actual grant does not go accordingly. As one example the caseof a grant to Case Number: 168 / Pdt.G / 2009 / PA.Pbr, concerning the cancellation of a plotof land according to the Islamic law which is in accordance with the provisions of theapplicable law or is not appropriate and to determine how the consideration of the judges inCivil judge No. 168 / Pdt.G / 2009 / PA.Pbr, whether the judge's decision has met theprinciple of legal certainty in the cancellation of the grant a piece of land according to Islamiclaw ruling Case Number 168 / Pdt.G / 2009 / PA.Pbr. This type of research is a normativelaw, namely the study of the level of legal synchronization. In this study the authors used atechnique research literature (Library Research) supported by secondary data according to itspower divided into three Haban law, namely the primary legal materials, secondary law, andtertiary legal materials.From the results of research on the religious court decisions pekanbaru the casenomor168 / Pdt.G / 2009 / PA.Pbr. grants of land and buildings thereon permanent home withGrant Act No. 282/2008 on December 2, 2008, which has been granted or be declaredcanceled or revoked as the joint property of husband and wife, for the purpose ofpenghibahhan not materialize. Judge to consider revocation or cancellation of the grant due tothe grants given to children - his son for the form and purpose of peace between husband andwife are not the occurrence of a divorce, but because of the prodigal son to his parents, underArticle 212 Compilation of Islamic law so it has no legal power premises so the Court ruledthat the grant deed legally canceled.Keywords: Cancellation Grant, Law, Islam